Transforming education for Generation Z: traditional character-based at Pesantren - Khunaivi, Herman; Rakhmawati, Intan Aulia; Hidayah, Syarifatul Fitri (UIN Salatiga, 2025)
This study aims to describe the educational transformation at the Pesantren Al-Anwar III Sarang Rembang in facing the challenges of Generation Z through a traditionally oriented character-based. The research method used was descriptive quantitative with a questionnaire instrument that had been tested for validity and reliability, covering three leading indicators: internalization of traditional character values, integration of technology in learning, and the suitability of the educational approach to the characteristics of Generation Z. The results showed that the internalization of traditional character values o btained the highest percentage of 70.22%, reflecting the success of the Pesantren in maintaining Islamic values and traditions. Meanwhile, the integration of technology and the suitability of the educational approach obtained 57.13% and 57.04%, indicating that innovation and adaptation to the needs of Generation Z have begun but still need strengthening. Pesantren Al-Anwar III Sarang Rembang had attempted educational transformation through project-based learning activities, digital literacy, and collaboration with external institutions. However, infrastructure limitations and resistance to change were still challenges. This study emphasized that Pesantren education development in the modern era must be carried out with a selective approach, namely, maintaining fundamental values w hile adopting relevant and contextual innovations.